2010
DOI: 10.1002/eej.21071
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrode material on pressure‐rise due to arc in a closed chamber

Abstract: SUMMARYThis paper describes the phenomenon of internal pressure-rise due to arcs ignited between metal rod electrodes in air. First, the internal pressure-rises in a closed chamber due to arcs were measured at currents within the range of 1 to 12.5 kA. The rod electrodes were made of copper, iron, and aluminum, and were 20 mm in diameter. The measurements showed that the maximum pressure-rise distinctly differed with each electrode material at the same total arc energy, namely, the maximum pressure-rise was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…When compared with the case without erosion, the calculated pressure rise becomes severely lower for Fe, almost unchanged for Cu, and drastically higher for Al. This is mainly attributable to the change of energy balance in the fault arc [1,3].…”
Section: Radiation Loss and Pressure Risementioning
confidence: 99%
See 3 more Smart Citations
“…When compared with the case without erosion, the calculated pressure rise becomes severely lower for Fe, almost unchanged for Cu, and drastically higher for Al. This is mainly attributable to the change of energy balance in the fault arc [1,3].…”
Section: Radiation Loss and Pressure Risementioning
confidence: 99%
“…It may not only seriously damage the installation and equipment, but also threaten the operative's personal safety. The pressure rise due to internal arcing is seriously affected by the energy balance of the fault arc [1,2]. The fault arc dissipates a part of the power via a radiation process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, our institute conducted experimental studies on pressure rise characteristics in closed chambers and developed simulations for pressure rise and propagation using a CFD (computational fluid dynamics) tool. We investigated the effects of various parameters on pressure rise and propagation and confirmed that the pressure rise and propagation can be predicted by appropriate setting of such parameters, especially the percentage of arc energy contributing to the heating of air inside the chamber.…”
Section: Introductionmentioning
confidence: 99%